2021
DOI: 10.3390/foods10010112
|View full text |Cite
|
Sign up to set email alerts
|

Artichoke Biorefinery: From Food to Advanced Technological Applications

Abstract: A sequential extraction process has been designed for valorizing globe artichoke plant residues and waste (heads, leaves, stalks, and roots left in the field) by means of green extraction techniques according to a biorefinery approach. We investigated two cascading extractions based on microwave-assisted extractions (MAE) and green solvents (water and ethanol) that have been optimized for varying temperature, solvent and extraction time. In the first step, phenols were extracted with yields that ranged between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 54 publications
4
28
0
Order By: Relevance
“…In the last years, non-conventional extraction techniques, such as PLE, MAE and supercritical fluid extraction (SFE), have also been applied for the extraction from artichoke wastes [ 61 , 63 , 71 ]. In particular, PLE and MAE have been applied to the extraction of inositols and inulin from artichoke bracts.…”
Section: Extraction Methods Of Antioxidants From Food Waste: Towards ...mentioning
confidence: 99%
See 2 more Smart Citations
“…In the last years, non-conventional extraction techniques, such as PLE, MAE and supercritical fluid extraction (SFE), have also been applied for the extraction from artichoke wastes [ 61 , 63 , 71 ]. In particular, PLE and MAE have been applied to the extraction of inositols and inulin from artichoke bracts.…”
Section: Extraction Methods Of Antioxidants From Food Waste: Towards ...mentioning
confidence: 99%
“…In a recent study, Francavilla et al [ 63 ] investigated two cascading extraction methods based on MAE in hydroethanolic mixtures, aiming to improve temperature, solvent and extraction time conditions. An aqueous solution, a 100% EtOH solution and three different EtOH/H 2 O mixtures (25, 59 and 75%, v / v ) were used at three different temperatures (50, 75 and 100 °C) with three different extraction times (5, 10 and 20 min) [ 63 ]. The process, designed for valorizing different globe artichoke plant residues, was conducted in two steps.…”
Section: Extraction Methods Of Antioxidants From Food Waste: Towards ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, the amount of bioactive components passing into the solvent in concentrated extracts was reported to be high [10]. A past study about total phenolic content in ethanol extracts of the artichoke demonstrated that the extracts were rich in total phenolic (32.2 mg GAE/g) [24,25]. Curadi et al [26] found that total phenolic content in artichoke byproducts were found to be between 7.31 and 13.05 mg/g in the methanol extracts as chlorogenic acid equivalent.…”
Section: Total Phenolic and Flavonoid Analysis In Extractsmentioning
confidence: 99%
“…Another paper of this Special Issue is focused on the use of artichoke crop residues as raw materials for the production of valuable compounds, specifically phenols and inulin [ 19 ]. Inulin is a natural storage polysaccharide in plants that is considered a prebiotic compound which is indigestible by humans but stimulates the growth and activity of specific microorganisms of the colon [ 20 ].…”
mentioning
confidence: 99%